2011
DOI: 10.1111/j.1478-5153.2010.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of the impact of nurse practitioners in critical care services

Abstract: Internationally, Critical Care Nurse Practitioners are demonstrating substantial positive patient, service and nursing outcomes. Critical Care Nurse Practitioner models were cost effective, appropriate and efficient in the delivery of critical care services. RELEVANCE TO CLINICAL PRACTISE: In Australia, there was minimal evidence of Critical Care Nurse Practitioner impact on adult, paediatric or neonatal intensive care units. The international evidence suggests that the contribution of the role needs to be str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 38 publications
2
35
0
8
Order By: Relevance
“…150,151 Moreover, the integration of advanced practice providers (nurse practitioners and physician assistants) into the cardiac critical care team can improve patient outcomes, including reduced length of stay and decreased complications, particularly among the chronically critically ill population. [152][153][154] Advanced practice providers with specific training and experience in cardiac conditions contribute to cost-effective care, improved staffing, and continuity of care.…”
Section: Nursing Advanced Practice Providers Pharmacy and Other Stmentioning
confidence: 99%
“…150,151 Moreover, the integration of advanced practice providers (nurse practitioners and physician assistants) into the cardiac critical care team can improve patient outcomes, including reduced length of stay and decreased complications, particularly among the chronically critically ill population. [152][153][154] Advanced practice providers with specific training and experience in cardiac conditions contribute to cost-effective care, improved staffing, and continuity of care.…”
Section: Nursing Advanced Practice Providers Pharmacy and Other Stmentioning
confidence: 99%
“…12,14,15 On a daily basis, in an effort to reduce hospital length of stay, mortality and morbidity, and hospital readmission rates, the ACNP is constantly evaluating avenues to contain cost while providing safe and efficient care, increase patient satisfaction, and ensure the plan of care comprises action plans to ensure patient safety. 8,10,12,16,17 As a result of the ACNP's consistent vigilance over these clinical indicators, patients who received care from ACNPs had the same clinical outcomes as patients who were managed by hospitalist-led care. 14,17 This case study highlights the role of an ACNP caring for an acutely ill patient hospitalized over 70 days.…”
Section: Review Of the Literaturementioning
confidence: 90%
“…Studies have consistently found that NPs can deliver primary care comparable to that provided by primary care physicians at equal or better quality and lower cost (Dierickvan Daele, Metsemakers, Derckx, Spreeuwenberg, & Vrijhoef, 2009;Flaskerud, 2010;Fry, 2011;Mundinger et al, 2000;Rossiter, 2013). The literature indicates that NPs provide effective, high-quality care and can safely supplement physician care to increase healthcare access in the United States.…”
Section: Current Relevance Of the Np Rolementioning
confidence: 96%